Collaborative Regulation of LRG1 by TGF-β1 and PPAR-β/δ Modulates Chronic Pressure Overload–Induced Cardiac Fibrosis. (December 2019) - Liu, Chenghao; Lim, Seok Ting; Teo, Melissa Hui Yen; Tan, Michelle Si Ying; Kulkarni, Madhura Dattatraya; Qiu, Beiying; Li, Amy; Lal, Sean; dos Remedios, Cristobal G.; Tan, Nguan Soon; Wahli, Walter; Ferenczi, Michael Alan; et al.
Abstract : Background: Despite its established significance in fibrotic cardiac remodeling, clinical benefits of global inhibition of TGF (transforming growth factor)-β1 signaling remain controversial. LRG1 (leucine-rich-α2 glycoprotein 1) is known to regulate endothelial TGFβ signaling. This study evaluated the role of LRG1 in cardiac fibrosis and its transcriptional regulatory network in cardiac fibroblasts. Methods: Pressure overload–induced heart failure was established by transverse aortic constriction. Western blot, quantitative reverse transcription polymerase chain reaction, immunofluorescence, and immunohistochemistry were used to evaluate the expression level and pattern of interested targets or pathology during fibrotic cardiac remodeling. Cardiac function was assessed by pressure-volume loop analysis. Results: LRG1 expression was significantly suppressed in left ventricle of mice with transverse aortic constriction–induced fibrotic cardiac remodeling (mean difference, −0.00085 [95% CI, −0.0013 to −0.00043]; P =0.005) and of patients with end-stage ischemic-dilated cardiomyopathy (mean difference, 0.13 [95% CI, 0.012–0.25]; P =0.032). More profound cardiac fibrosis (mean difference, −0.014% [95% CI, −0.029% to −0.00012%]; P =0.048 for interstitial fibrosis; mean difference, −1.3 [95% CI, −2.5 to −0.2]; P =0.016 for perivascular fibrosis), worse cardiac dysfunction (mean difference, −2.5 ms [95% CI, −4.5 to −0.4 ms]; P =0.016 for Tau-g; mean difference, 13% [95% CI, 2%–24%]; P =0.016 for ejection fraction), and hyperactive TGFβ signaling in transverse aortic constriction–operated Lrg1 -deficient mice (mean difference, −0.27 [95% CI, −0.47 to −0.07]; P <0.001), which could be reversed by cardiac-specific Lrg1 delivery mediated by adeno-associated virus 9. Mechanistically, LRG1 inhibits cardiac fibroblast activation by competing with TGFβ1 for receptor binding, while PPAR (peroxisome proliferator-activated receptor)-β/δ and TGFβ1 collaboratively regulate LRG1 expression via SMRT (silencing mediator for retinoid and thyroid hormone receptor). We further demonstrated functional interactions between LRG1 and PPARβ/δ in cardiac fibroblast activation. Conclusions: Our results established a highly complex molecular network involving LRG1, TGFβ1, PPARβ/δ, and SMRT in regulating cardiac fibroblast activation and cardiac fibrosis. Targeting LRG1 or PPARβ/δ represents a promising strategy to control pathological cardiac remodeling in response to chronic pressure overload. Abstract : Supplemental Digital Content is available in the text.